Ethical leadership in and through labour, business and politics - Dames, GE (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
This article articulates the proceedings of three research based conferences on ethical leadership. The objective is to describe the notion of ethical leadership in labour, business and politics. Firstly, the current context will be addressed; secondly, the ethical challenge in Labour will be described; thirdly, ethical challenges in Business will be discussed; fourthly, the ethical question in Politics will be addressed; and finally, the discussion will be summarised and concluded. The following dynamics are illustrations of our moral challenges: (1) Private accumulation of material wealth and power as a onslaught on values; (2) The development of a new philosophy of patriotism and nationalism; (3) Labour, business and politics should become contributors and not detractors; (4) Corporate social capital and responsibility for the good of everybody; and (5) Labour, business and politics should become ‘reputational capital’ agencies to realise the basic needs of human beings.